1992
DOI: 10.1172/jci115741
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial restitution. Characterization of a cell culture model and mapping of cytoskeletal elements in migrating cells.

Abstract: Closure of superficial wounds in epithelia occurs by migration of cells shouldering the wound. We describe an in vitro model of such restitution using a human intestinal epithelial cell line,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(183 citation statements)
references
References 35 publications
11
171
0
1
Order By: Relevance
“…Because villin has a higher affinity for PIP 2 than PLC-␥ 1 , villin could sequester PIP 2 and release PIP 2 following tyrosine phosphorylation (in response to receptor activation) and thus play a role as a signal-generating actin-regulatory protein (33). (iii) Villin is localized to the leading edge of intestinal epithelial cells (73,74). Association of villin with PIP 2 could regulate actin assembly in the vicinity of the plasma membrane by inhibiting severing and capping, thus accelerating actin assembly, and by increasing actin bundling it can stabilize the cell surface protrusion, thus regulating cell shape change as well as cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…Because villin has a higher affinity for PIP 2 than PLC-␥ 1 , villin could sequester PIP 2 and release PIP 2 following tyrosine phosphorylation (in response to receptor activation) and thus play a role as a signal-generating actin-regulatory protein (33). (iii) Villin is localized to the leading edge of intestinal epithelial cells (73,74). Association of villin with PIP 2 could regulate actin assembly in the vicinity of the plasma membrane by inhibiting severing and capping, thus accelerating actin assembly, and by increasing actin bundling it can stabilize the cell surface protrusion, thus regulating cell shape change as well as cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…In the gastrointestinal mucosa, cell proliferation and migration play a fundamental role in the organization and maintenance of tissue integrity (50). When damaged, the gastrointestinal mucosa has a remarkable ability to repair itself very rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…ITF is a cytoprotective peptide secreted by intestinal goblet cells [16]. ITF has an important role during intestinal epithelial migration [12,17], a major step of the restitution process [32], but its mechanism of action remains unclear. Previous investigations showed that intestinal epithelial cells constitutively release NO in itro [33,34].…”
Section: Discussionmentioning
confidence: 99%